Effects of Antimony on Reactive Oxygen and Nitrogen Species (ROS and RNS) and Antioxidant Mechanisms in Tomato Plants - Espinosa-Vellarino, Francisco L.; Garrido, Inmaculada; Ortega, Alfonso; Casimiro, Ilda; Espinosa, Francisco (Frontiers in Plant Science, 2020)
This research studies the effects that Sb toxicity (0.0, 0.5, and 1.0 mM) has on the growth, reactive oxygen and nitrogen species, and antioxidant systems in tomato plants. Sb is accumulated preferentially in the roots, with little capacity for its translocation to the leaves where the concentration is much lower. The growth of the seedlings is reduced, with alteration in the content in other nutrients. There is a decrease in the content of Fe, Mg, and Mn, while Cu and Zn increase. The contents in chlorophyll a and b decrease, as does the photosynthetic efficiency. On the contrary the carotenoids increase, indicating a possible action as antioxidants and protectors against Sb. The phenolic compounds do not change, and seem not to be involved in the defense response of the tomato against the stress by Sb. The water content of the leaves decreases while that of proline increases in response to the Sb toxicity. Fluorescence microscopy images and spectrofluorometric detection showed increases in the production of O2.–, H2O2, NO, and ONOO–, but not of nitrosothiols. The Sb toxicity induces changes in the SOD, POX, APX, and GR antioxidant activities, which show a clear activation in the roots. In leaves, only the SOD and APX increase. The DHAR activity is inhibited in roots but undergoes no changes in the leaves, as is also the case for the POX and GR activities. Ascorbate increases while GSH decreases in the roots. The total AsA + DHA content increases in the roots, but the total GSH + GSSG content decreases, while neither is altered in the leaves. Under Sb toxicity increases the expression of the SOD, APX, and GR genes, while the expression of GST decreases dramatically in roots but increases in leaves. In addition, an alteration is observed in the pattern of the growth of the cells in the elongation zone, with smaller and disorganized cells. All these effects appear to be related to the ability of the Sb to form complexes with thiol groups, including GSH, altering both redox homeostasis and the levels of auxin in the roots and the quiescent center.